Virtual Reality Tour Sebagai Media Informasi Pengenalan Gedung Kampus 2 Universitas 'Aisyiyah Surakarta - Aisyah Mutia Dawis (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2022)
In this era of modernization, technology is a very important aspect, almost every line of life requires the help of technology to make work easier. Through technology, almost every information in the world can be accessed easily and quickly. The information obtained is not only in the form of text, but it can also be in other forms such as images or photos or videos. One type of photo technology, namely 360-degree Virtual Reality (VR) photos, with Virtual Reality can make someone feel as if they are in the real world through this technology. Making a virtual reality tour with the panoramic image method for the ‘Aisyiyah University of Surakarta Campus 2 serves as a form of campus information media that is displayed in the form of a 360-degree panoramic image. The research method used in this study is the Multimedia Development Life Cycle (MDLC) methodology which is the most appropriate method by emphasizing the 6 stages of development, namely concept, design, data collection, installation, testing, and distribution. The need for making this virtual reality tour uses hardware in the form of cellphones, lenses, panoramic gimbals and laptops as well as software such as photoshop, panoweaver, 3sixty, xampp and sublime text.